Customer Satisfaction Index of Singapore: Executive Summary 2007 - Institute of Service Excellence, SMU (Institutional Knowledge at Singapore Management University, 2008)
The Institute of Service Excellence at Singapore Management University was appointed by the Workforce Development Agency (WDA) to implement and maintain an annual benchmark for service related industries in Singapore. The 2007 Customer Satisfaction Index of Singapore (CSISG 2007) is based on data from a nationwide survey conducted between May 1 and July 23 2007. This survey was designed by the National Quality Research Center (NQRC) at the University of Michigan and modeled after the American Customer Satisfaction Index (ACSI).